Hydrochar and Humic Acid as Template of ZnAl Layered Double Hydroxide for Adsorption of Phenol - Muhammad Badaruddin; Nur Ahmad; Erni Salasia Fitri; Aldes Lesbani; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
The adsorbents potential ZnAl-LDH, ZnAl-Hydrochar, and ZnAl-Humic acid were prepared using the coprecipitation method. The adsorbents were characterization by XRD, FTIR, and BET analysis. XRD peaks of ZnAl-LDH at 10.29°, 20.07°, 29.59°, 32.12°, 34.02°, 48.06°, and 60.16°. The FTIR absorption peak was observed at 3400-3500 cm−1, 1600-1700 cm−1, 1381 cm−1, 1000 cm−1, 500-700 cm−1. All adsorbents exhibited N2 adsorption-desorption isotherms type IV classified as a mesoporous structure (pore size= 2-50 nm). The surface areas of composites were higher than LDH and following order: ZnAl-Hydrochar > ZnAl-Humic acid > ZnAl-LDH. The kinetic parameter showed the pseudo-second-order kinetics model. The maximum adsorption capacity of ZnAl-LDH, ZnAl-Hydrochar, and ZnAl-Humic acid were 48.077 mg/g, 90.090 mg/g, 94.340 mg/g, respectively; with Freundlich isotherm model. Reusability after 5 times of ZnAl-LDH, ZnAl-Hydrochar, and ZnAl-Humic acid in the range 49.81-0.890%, 95.92-9.84%, and 70.02-5.72%, respectively. The adsorbent can be used up to 3 times.